Distribution of Electrical Conductivity in Mammalian Muscle Tissue Model on Exposed to a Pulsed Electric Field - warindi, warindi (PROtek : Jurnal Ilmiah Teknik Elektro, 2017)
Biological cells has natural characteristic to isolate subtances between outside and inside cell by using its membranes. By applying pulsed electric field, membrane pores can be formed that facilitates the introduction of small foreign materials into cells. The success of this technique can be determined by observation of conductivity changes. The equivalent conductance can be measured but the unhomogeneous electric field results unhomogeneous conductance. The aim of this research is to compute conductivity distribution on a specific biological tissue (e.g. mammalian muscle tissue) that being electrically pulsed. The tissue is modeled as conductive medium due to its conductivity dominant. The medium as a system of electrocondusive, modeling of this system leads to get a model in the form of partial different equation problems. A finite element method is used as a tool to solve the problem. The final simulation result are graphical presentations showing the conductance. It is also shown that the intensity of the field is higher in the location near electrode and smaller in remote location. Then, electrical conductivity, derived from electric field exposure is then can be computed. It is shown that needle electrodes exibit inhomogeneous conductivity distribution. A large increase of conductivity occurs surrounding both electrodes and much smaller increase on other location. A larger conductivity change means more number and size of pores are produced. In practical aspect, the result can be further developed for designing in-vivo pulsed electric field applications